Role of Cultural Resources in Mental Health: An Existential Perspective - Shukla, Shashwat (Frontiers in Psychology, 2022)
The role of cultural resources in mental health is vital. Often, this role is underestimated by taking a reductionist view of mental health. To promote sustainable and enduring mental health the deeper, existential aspects of mental health need to be given space in the mental health discourse. This paper explores how such spaces can be created by looking at the case of Indic festivals and the role they play in mental health as per the timeless healing modalities of Yoga & Ayurveda.